Key Terrestrial and Space Environment Sources - Johnson,Dale L. (2020)
ABSTRACT Natural (Terrestrial & Space) Environment (NE) phenomena play a significant role in the design and flight of aerospace vehicles and in the integrity of the associated aerospace systems and structures. Both the terrestrial environment (0-90 km altitude) and the space environment (Earth orbital altitudes) parameters and their engineering application philosophy are given with emphasis on launch vehicle-affected terrestrial environment elements. This paper will describe the key terrestrial and space environment sources: wind; atmospheric; and orbital models used in the design and development of launch/space vehicles.